The The Predictive Role of Sociodemographic Factors in Nurses' Psychological Hardiness - Ali, Noor; Husseian, Iman (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): The study aims to identify the role of sociodemographic factors in predicting the level of psychological hardiness of nurses.Methodology: A descriptive correlational study conducted in the Medical City hospitals in the city of Baghdad during the period from November 1, 2022 to May 1, 2023 on a sample of 156 male and female nurses.  The validity of the questionnaire was verified by presenting it to experts, and its reliability was verified through a pilot study.  Data analysis was carried out using (SPSS, version 26) program.Results: Results showed that (57.7%) of nurses reported a moderate level of psychological hardiness, (42.3%) are associated with high level of psychological hardiness. Also the study found no significant difference between nurses' age, gender, marital status, socioeconomic status, qualification, workplace, and years of experience and their overall psychological hardiness score.Conclusion: The study concluded that socio-demographic factors do not affect the level of psychological hardiness among nurses.Recommendations: To further investigate the impact of demographic and work-related factors on psychological hardiness, future research should include larger and more diverse samples of nurses, particularly those from different cultural and socioeconomic backgrounds. Keywords: Psychological Hardiness, Sociodemographic Factors, Nurses